Analysis The Effect of Village Funds on Accelerating Economic Development in Rural Areas - Lamba, Arung; Lamba, Marsal Arung (Apollo: Journal of Tourism and Business, 2025)
This research intends to examine the impact of Village Fund utilization on accelerating economic development in rural areas. The Village Fund is a strategic government policy to improve the welfare of rural communities through infrastructure development, economic empowerment, and job creation. This research applies a quantitative method supported by a Likert scale questionnaire distributed to 100 respondents in three villages in Jayapura Regency. The method of analysis is simple linear regression using SPSS software program. The results of the study indicate that the utilization of Village Funds has a positive and significant effect on accelerating rural economic development, showing a regression coefficient of 0.512 and p-value of 0.000. The R² value of 0.399 demonstrates that 39.9% of economic growth variability is accounted for by the utilization of Village Funds, while the remainder is influenced by other factors. This finding emphasizes the importance of transparent management of Village Funds oriented toward productive sectors to create self-reliant and competitive villages